White matter lesions in magnetic resonance imaging of the brain in 56 patients with visual vertigo. Issue 6 (18th July 2018) - Dimitriadis, P A; Saad, M; Igra, M S; Mandavia, R; Bowes, C; Hoggard, N; Ray, J
Abstract: Background: Visual vertigo is defined as a condition in which there is worsening or triggering of vestibular symptoms in certain visual environments. Previous studies have associated visual vertigo with an increased prevalence of underlying white matter lesions on brain imaging. Method: This study evaluated the magnetic resonance imaging scans of the brain from a cohort of patients with visual vertigo, and compared the outcomes to an age- and gender-matched group of healthy volunteers. Results and conclusion: White matter lesions were observed in 17.9 per cent of the patient group and in 16.3 per cent of the control group. The prevalence of white matter lesions in the patient group was not too different to that expected based on age.